Risk Analysis of Emergency Based on Fuzzy Evidential Reasoning - Xiaojiao Qiao; Dan Shi (Complexity)
Risk analysis of emergency is vital to effective emergency management. However, conventional analysis is challenged by the emerging problems as risk of emergency appearing increasingly complicated. The risk attributes of emergency originate in complicated sources, and their information is always incomplete. To ensure the efficiency and stability of emergency risk analysis, we proposed an elaborative approach composed of structural description framework and fuzzy evidential reasoning. Firstly, the risk attributes are identified by structural description framework. The information as evidence is obtained and normalized for further analysis. Secondly, risk analysis model with fuzzy evidential reasoning is constructed, and risk grade is evaluated. Finally, a certain railway project accident is taken as an example to test the model and some managerial insights are demonstrated. An approach combining structural description framework and fuzzy evidential reasoning model is feasible and effective; furthermore, it provides stable support for emergency risk analysis.